1979
DOI: 10.1017/s0021859600060585
|View full text |Cite
|
Sign up to set email alerts
|

Lactation pattern in Scottish Blackface and East Friesland × Scottish Blackface cross-bred ewes

Abstract: SummaryMilk yield of 2-year-old Scottish Blackface and of East Friesland × Scottish Blackface ewes rearing single or twin lambs was estimated by the oxytocin method on 1 day each week up to the 14th week of lactation. Both groups of ewes had been reared from birth under good nutritional conditions. They were housed in individual pens from mid-pregnancy and offered a liberal ration of a pelleted concentrate food until parturition. Similar food was offered ad libitum during lactation.The cross-bred ewes rearing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 14 publications
4
5
0
Order By: Relevance
“…This is consistent with other studies (Peart, Doney and Smith, 1979;Foot and Russel, 1979) and presumably reflects the effects of twin pregnancy on live weight at lambing combined with subsequent higher milk production of ewes nursing twins. This is consistent with other studies (Peart, Doney and Smith, 1979;Foot and Russel, 1979) and presumably reflects the effects of twin pregnancy on live weight at lambing combined with subsequent higher milk production of ewes nursing twins.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with other studies (Peart, Doney and Smith, 1979;Foot and Russel, 1979) and presumably reflects the effects of twin pregnancy on live weight at lambing combined with subsequent higher milk production of ewes nursing twins. This is consistent with other studies (Peart, Doney and Smith, 1979;Foot and Russel, 1979) and presumably reflects the effects of twin pregnancy on live weight at lambing combined with subsequent higher milk production of ewes nursing twins.…”
Section: Discussionsupporting
confidence: 92%
“…Peart et al (1979) showed that ewes rearing two lambs consumed proportionately Oil more of a pelleted diet over the first 6 weeks of lactation than ewes with singles; similarly Foot and Russel (1979) reported a proportionally higher intake (009) for ewes rearing twins over the first 11 weeks of lactation. Peart et al (1979) showed that ewes rearing two lambs consumed proportionately Oil more of a pelleted diet over the first 6 weeks of lactation than ewes with singles; similarly Foot and Russel (1979) reported a proportionally higher intake (009) for ewes rearing twins over the first 11 weeks of lactation.…”
Section: Discussionmentioning
confidence: 99%
“…The linear regression coefficient of the mean daily milk production increased significantly (P<O.Ol) with increasing ewe body weight. This significant regression was in agreement with that found by Peart et al (1979).…”
Section: Resultssupporting
confidence: 93%
“…Although these results have confirmed the confounding of lamb demand and ewe milk production potential on the measured milk yield, the differences both in absolute level and in pattern of lactation between a dairy-type crossbred and a non-dairy pure breed, which were reported by Peart et al (1979), have been shown to be significant irrespective of the effect of lamb genotype. As in the previous study, peak yield was higher in the EFX ewes, within breed of lamb suckled, than in the BF ewes and the yield was more sustained during the declining stage of lactation.…”
Section: Discussionmentioning
confidence: 63%